Introducing the Neurology Milestones 2.0. (1st March 2022) - Dewey, Jeffrey J.; Chiota-McCollum, Nicole; Barratt, Diana; Edgar, Laura; Gutmann, Laurie; Shelgikar, Anita V.; Ward, Jayne; Kilgore, Shannon M.; ,
Abstract : The turn of the 21st century heralded a new era in medical education. The Institute of Medicine reports To Err is Human and Crossing the Quality Chasm called for reform of the health care system to improve the quality and safety of patient care. 1, 2 Concurrently, interest in competency-based medical education increased, and the alignment of an outcomes-based approach to education with the Institute for Healthcare Improvement's "Triple Aim" of health care set the stage for the ongoing transformation in medical education. 3, 4 A major component of this transformation, specific to graduate medical education (GME), has been the Next Accreditation System (NAS) of The Accreditation Council for Graduate Medical Education (ACGME).